2009
DOI: 10.1074/jbc.m109.010744
|View full text |Cite
|
Sign up to set email alerts
|

Neuroserpin Polymers Activate NF-κB by a Calcium Signaling Pathway That Is Independent of the Unfolded Protein Response

Abstract: The autosomal dominant dementia familial encephalopathy with neuroserpin inclusion bodies is characterized by the accumulation of ordered polymers of mutant neuroserpin within the endoplasmic reticulum of neurones. We show here that intracellular neuroserpin polymers activate NF-B by a pathway that is independent of the IRE1, ATF6, and PERK limbs of the canonical unfolded protein response but is dependent on intracellular calcium. This pathway provides a mechanism for cells to sense and react to the accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
113
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 68 publications
(124 citation statements)
references
References 46 publications
8
113
1
Order By: Relevance
“…Beneficial effects of active ATF6 in the clearance of serpin polymers have recently been shown in cells thus supporting our finding of selective UPR activity (Smith et al 2011). The induction of all three branches of the UPR is controversial for serpinopathies, with several reports showing absence (Davies et al 2009; Kroeger et al 2009) or presence of the UPR (Lawless et al 2004). Instead, an ER stress response distinct from classical UPR signaling has been reported (Davies et al 2009).…”
supporting
confidence: 70%
See 3 more Smart Citations
“…Beneficial effects of active ATF6 in the clearance of serpin polymers have recently been shown in cells thus supporting our finding of selective UPR activity (Smith et al 2011). The induction of all three branches of the UPR is controversial for serpinopathies, with several reports showing absence (Davies et al 2009; Kroeger et al 2009) or presence of the UPR (Lawless et al 2004). Instead, an ER stress response distinct from classical UPR signaling has been reported (Davies et al 2009).…”
supporting
confidence: 70%
“…The transient, agedependent induction of the UPR suggests the necessity of a second insult, possibly aging, to mount an UPR response. This finding unifies current concepts of disturbed proteostasis in FENIB (Lawless et al 2004;Hidvegi et al 2005;Davies et al 2009). Since IRE1 signaling has been linked to autophagy, the relatively low induction of IRE1 signaling in our murine FENIB model may help to explain the fact that autophagy is only mildly increased in FENIB (Hetz et al 2009;Kroeger et al 2009).…”
supporting
confidence: 49%
See 2 more Smart Citations
“…Instead Z α 1 -antitrypsin expression activates NFκB by a calcium-mediated pathway that is independent of the UPR [32][33][34][35]. We have termed this the 'ordered protein response' [35] and others have shown that it results in the release of IL-6 and IL-8 [34].…”
Section: Intracellular Processing Of α α α α 1 -Antitrypsin Polymersmentioning
confidence: 99%